2022
DOI: 10.1101/2022.12.27.521981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early excitatory and inhibitory modifications in the motor cortex following skill learning support motor memory consolidation and cortical plasticity overnight

Abstract: The learning of new motor skills constitutes an inseparable part of our lives. Motor consolidation refers to the offline processing of motor memories following the acquisition of new motor skills. The animal literature suggests that the primary motor cortex (M1) plays a key role in motor memory consolidation, and structural and functional plasticity in M1 following motor consolidation have been demonstrated. However, the mechanisms supporting motor memory consolidation and plasticity in the human M1 are not we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“…While those later findings are not directly related to reactivation or reconsolidation of existing motor memories, they further support the mechanistic link between the functionality of the GABAergic system and the potential to induce learning-related behavioral changes 24 . Lastly, our results are also in line with previous works demonstrating the importance of M1 processing during the early stages of initial motor memory consolidation, when the memory trace is still in an unstable state 15,21 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…While those later findings are not directly related to reactivation or reconsolidation of existing motor memories, they further support the mechanistic link between the functionality of the GABAergic system and the potential to induce learning-related behavioral changes 24 . Lastly, our results are also in line with previous works demonstrating the importance of M1 processing during the early stages of initial motor memory consolidation, when the memory trace is still in an unstable state 15,21 .…”
Section: Discussionsupporting
confidence: 93%
“…Motor learning in humans has been previously characterized by GABAergic-mediated cortical disinhibition during learning 12,13 . Furthermore, recent findings in humans have demonstrated that the initial consolidation of motor memories may also depend on increased cortical excitation and GABAergic decrease that take place offline early following learning 15 , possibly reflecting the role of neuronal excitation in the facilitation of synaptic plasticity processes [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following its reactivation, a memory trace has been shown to become labile again and prone to modifications ( 6 , 8 11 ), and reconsolidation is needed in order to restabilize it (i.e., making the memory once again resistant to interference) and promote skill improvements that develop after the practice session (i.e., offline learning gains). Neural excitation and inhibition (E-I) have been suggested to play a key role in the acquisition and consolidation of new motor skills in both animals and humans ( 12 15 ); we have therefore hypothesized they also play a fundamental role during the reconsolidation initiated by a brief reactivation. Changes in glutamate (Glu) and γ-aminobutyric acid (GABA), the main excitatory and inhibitory neurotransmitters in the brain, have been documented in the primary motor cortex (M1) both during ( 12 , 13 ) and following ( 14 , 15 ) the initial acquisition of motor skills.…”
mentioning
confidence: 99%